The Effect of Red Spinach Extract (Amaranthus tricolor L.) on Serum Malondialdehyde of Male Rattus Novergicus Fracture Model - Aris Prasetyo; Ahmad Baihaqi; Laksmi Indreswari (Faculty of Medicine, University of Jember, 2020)
Fracture is a musculoskeletal injury with a high incidence rate. The healing process of fracture is disturbed by the oxidative stress, because of imbalance quantity of Reactive Oxygen Species (ROS) and antioxidant capacity in the body that neutralizes it. Antioxidants in red spinach have the potential to suppress the level of oxidative stress. The study aimed to determinate the effect of red spinach ethanolic extract on decreasing oxidative stress by measuring malonaldialdehyde (MDA) concentration in fracture healing process. The study used thirty rats and divided into five groups; negative control group, positive control group,and three treatment groups of red spinach ethanolic extract in a dose of 35,4 mg/150gBB, 70,8 mg/150gBB, and 141,6 mg/150gBB manually fractured on right femur under anaesthesia and immobilized by leucodur plaster. Each group was treated orally respectively one week. The result of One Way Anova showed a significance of 0,000 (p<0,05) in which there was a significant difference in serum MDA levels between the treatment groups and the control groups. The result of LSD test between P1 group and P3 group showed significantly different in which decreased serum MDA levels were consistent with increasing doses of red spinach ethanolic extract. The study concluded that red spinach ethanolic extract had a positive effect on supression of oxidative stress in fracture healing process. Keywords: Red spinach ethanolic extract, fracture healing process, MDA, ROS